Barriers to timely and safe blood transfusion for PPH patients: evidence from a qualitative study in Dhaka, Bangladesh - Akhter, Sadika; Anwar, Iqbal; Akter, Rashida; Kumkum, Feroza Akhter; Nisha, Monjura Khatun; Ashraf, Fatema; Islam, Ferdousi; Begum, Nazneen; Chowdhury, Mahbub Elahi; Austin, Anne; Islam, Syed Shariful; Rahman, Aminur (BRAC Univeristy, 2018)
This article was published in the PLoS ONE [© 2016 PLoS ONE] and the definite version is available at : https://doi.org/10.1371/journal.pone.0167399 . The Journal's website is at: http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0167399